Expression analysis of cinnamoyl-CoA reductase (CCR) gene in developing seedlings of Leucaena leucocephala: A pulp yielding tree species - Srivastava, Sameer; Gupta, Ranadheer K.; Arha, Manish; Vishwakarma, Rishi K.; Rawal, Shuban K.; Kishor, P. B. Kavi; Khan, Bashir Mohammad (Plant Physiology and Biochemistry, 2011)
Removal of lignin is a major hurdle for obtaining good quality pulp. Leucaena leucocephala (subabul) is extensively used in paper industry in India; therefore, as a first step to generate transgenic plants with low lignin content, cDNA and genomic clones of CCR gene were isolated and characterized. The cDNA encoding CCR (EC 1.2.1.44) was designated as LI-CCR; the sequence analysis revealed an Open Reading Frame (ORF) of 1005 bp. Phylogenetic analysis showed that LI-CCR sequence is highly homologous to CCRs from other dicot plants. The 2992 bp genomic clone of Leucaena CCR consists of 5 exons and 4 introns. The haploid genome of L leucocephala contains two copies as revealed by DNA blot hybridization. LI-CCR gene was over-expressed in Escherichia coli, which showed a molecular mass of approximately 38 kDa. Protein blot analysis revealed that LI-CCR protein is expressed at higher levels in root and in stem, but undetectable in leaf tissues. Expression of CCR gene in Leucaena increased up to 15 d in case of roots and stem as revealed by QRT-PcR studies in 0-15 d old seedlings. ELISA based studies of extractable CCR protein corroborated with QRT-PCR data. CCR protein was immuno-cytolocalized around xylem tissue. Lignin estimation and expression studies of 5,10 and 15 d old stem and root suggest that CCR expression correlates with quantity of lignin produced, which makes it a good target for antisense down regulation for producing designer species for paper industry. (C) 2010 Elsevier Masson SAS. All rights reserved.
Keywords: Cinnamoyl-CoA reductase; Developing seedling; Leucaena leucocephala; Lignin biosynthesis

Cinnamate 4-hydroxylase (C4H) genes from leucaena leucocephala: a pulp yielding leguminous tree - Kumar, Santosh; Omer, Sumita; Patel, Krunal; Khan, Bashir Mohammad (Molecular Biology Reports, 2013)
Leucaena leucocephala is a leguminous tree species accounting for one-fourth of raw material supplied to paper and pulp industry in India. Cinnamate 4-Hydroxylase (C4H, EC 1.14.13.11) is the second gene of phenylpropanoid pathway and a member of cytochrome P450 family. There is currently intense interest to alter or modify lignin content of L. leucocephala. Three highly similar C4H alleles of LlC4H1 gene were isolated and characterized. The alleles shared more than 98 % sequence identity at amino acid level to each other. Binding of partial promoter of another C4H gene LlC4H2, to varying amounts of crude nuclear proteins isolated from leaf and stem tissues of L. leucocephala formed two loose and one strong complex, respectively, suggesting that the abundance of proteins that bind with the partial C4H promoter is higher in stem tissue than in leaf tissue. Quantitative Real Time PCR study suggested that among tissues of same age, root tissues had highest level of C4H transcripts. Maximum transcript level was observed in 30 day old root tissue. Among the tissues investigated, C4H activity was highest in 60 day old root tissues. Tissue specific quantitative comparison of lignin from developing seedling stage to 1 year old tree stage indicated that Klason lignin increased in tissues with age.
Keywords: Cinnamate 4-Hydroxylase (C4H); Leucaena leucocephala; lignin; Phenylpropanoid

Functional characterization, homology modeling and docking studies of beta-glucosidase responsible for bioactivation of cyanogenic hydroxynitrile glucosides from Leucaena leucocephala (subabul) - Shaik, Noor M.; Misra, Anurag; Singh, Somesh; Fatangare, Amol B.; Ramakumar, Suryanarayanarao; Rawal, Shuban K.; Khan, Bashir Mohammad (Molecular Biology Reports, 2013)
Glycosyl hydrolase family 1 beta-glucosidases are important enzymes that serve many diverse functions in plants including defense, whereby hydrolyzing the defensive compounds such as hydroxynitrile glucosides. A hydroxynitrile glucoside cleaving beta-glucosidase gene (Llbglu1) was isolated from Leucaena leucocephala, cloned into pET-28a (+) and expressed in E. coli BL21 (DE3) cells. The recombinant enzyme was purified by Ni-NTA affinity chromatography. The optimal temperature and pH for this beta-glucosidase were found to be 45 A degrees C and 4.8, respectively. The purified Llbglu1 enzyme hydrolyzed the synthetic glycosides, pNPGlucoside (pNPGlc) and pNPGalactoside (pNPGal). Also, the enzyme hydrolyzed amygdalin, a hydroxynitrile glycoside and a few of the tested flavonoid and isoflavonoid glucosides. The kinetic parameters K (m) and V (max) were found to be 38.59 mu M and 0.8237 mu M/mg/min for pNPGlc, whereas for pNPGal the values were observed as 1845 mu M and 0.1037 mu M/mg/min. In the present study, a three dimensional (3D) model of the Llbglu1 was built by MODELLER software to find out the substrate binding sites and the quality of the model was examined using the program PROCHEK. Docking studies indicated that conserved active site residues are Glu 199, Glu 413, His 153, Asn 198, Val 270, Asn 340, and Trp 462. Docking of rhodiocyanoside A with the modeled Llbglu1 resulted in a binding with free energy change (Delta G) of -5.52 kcal/mol on which basis rhodiocyanoside A could be considered as a potential substrate.
Keywords: Glycosyl hydrolase family 1; homology modeling; Leucaena leucocephala; Molecular docking

Over-expression of a subgroup 4 R2R3 type MYB transcription factor gene from Leucaena leucocephala reduces lignin content in transgenic tobacco - Omer, Sumita; Kumar, Santosh; Khan, Bashir Mohammad (Plant Cell Reports, 2013)
LlMYB1 , a subgroup 4 R2R3-type MYB transcription factor gene from Leucaena leucocephala appears to be a repressor of lignin biosynthesis pathway by regulating the transcription of general phenylpropanoid pathway genes. R2R3MYB transcription factors are known to play a wide role in regulating the phenylpropanoid pathway in plants. In this study, we report isolation, cloning and characterization of an R2R3MYB transcription factor gene (LlMYB1) from an economically important tree species, Leucaena leucocephala. LlMYB1 consists of 705 bp coding sequence corresponding to 235 amino acids. Sequence alignment revealed that the N-terminal (MYB) domain of the gene shares up to 95 % similarity with subgroup 4 (Sg4) members of R2R3Myb gene family functionally known to be lignin repressors. Highly divergent C-terminal region of the gene carried an ERF-associated amphiphilic repression (EAR) motif, another characteristic of the Sg4. The gene was phylogenetically grouped closest with AmMYB308, a known repressor of monolignol biosynthetic pathway genes. Spatio-temporal expression studies at different ages of seedlings using quantitative real-time PCR (QRT-PCR) showed highest transcript level of the gene in 10 day old stem tissues. Over-expression of the gene in transgenic tobacco showed statistically significant decline in the transcript levels of the general phenylpropanoid pathway genes and reduction in lignin content. Our study suggests that LlMYB1 might be playing the role of a repressor of lignin biosynthesis in L. leucocephala.
Keywords: Leucaena leucocephala; lignin; R2R3MYB; Repressor; Transcript level